UNFAIR TERMS IN COMMERCIAL CONTRACTS: RESEARCH FINDINGS (World Conference on Social Sciences, Law and Public Policy, 2026)
The article examines unfair terms in commercial (B2B) contracts as an independent civil-law phenomenon that cannot be reduced to the doctrine of unconscionable transactions. It is argued that the prevailing focus on administrative, regulatory, and competition-law remedies addresses only the external dimension of the problem while leaving its private-law essence–namely, the structural inequality of bargaining power between contracting parties –ф –without an adequate legal response. Drawing on a comparative legal analysis and the author’s empirical research, the study substantiates the propositions that the “weaker party” in B2B relations is an integrative, contextual category and that the appropriate legal consequence is the partial invalidity of an unfair term while the contract as a whole is preserved. As a result, the author proposes a coherent package of amendments to the civil legislation of the Republic of Uzbekistan.
Keywords: unfair terms, commercial contract, freedom of contract, weaker party, good faith, digital platforms, superior bargaining power, partial invalidity, contract of adhesion, civil-law protection